Monitoring the pendulum between El Niño and La Niña events. (21st June 2018) - Su, Jingzhi; Lian, Tao; Zhang, Renhe; Chen, Dake
Abstract: The El Niño-Southern Oscillation (ENSO) pendulum swings back and forth between the El Niño and La Niña phenomena. To monitor the relative phase changes of the ENSO pendulum, 13 clusters are obtained based on the pattern of sea surface temperature anomalies (SSTAs) along the equatorial Pacific. The historical ENSO evolution can be effectively described by the alternation among those clusters. The zonal movement of SSTA loading during the ENSO evolution can also be captured by the changes in the clusters. One scheme was designed to monitor the ENSO pendulum based on those clusters as well the SSTAs in the Niño-3.4 region. When applied in practice to monitor historical ENSO events, including the 1997 El Niño and 2015 El Niño phenomena, the scheme tends be suitable for describing the ENSO pendulum between El Niño and La Niña, and it has the advantage of presenting both the ENSO amplitude and SSTA pattern.